The declamations of Calpurnius Flaccus : text, translation, and commentary - Calpurnius Flaccus. (Mnemosyne, Supplements, 1994)
The excerpts from the Declamations of Calpurnius Flaccus (2nd century A.D.) are one of our major sources of knowledge concerning controversiae , model court speeches on fictitious themes. These formed the focus of Roman higher education and therefore had an enormous effect on Latin literary style and content from the late Republic on. They also contain important indirect evidence for contemporary social history. This book provides a general introduction to the work, a new Latin text, plus the first English translation and only full modern commentary. The latter discusses the legal background and origins of the cases, points at issue, textual problems, and matters of Latin style. The volume will therefore be of interest to students of classical rhetoric, education, history, and philology.